Editorial Open Praxis Volume 14 Issue 4 - Inés Gil-Jaurena (Open Praxis, 2022)
This Open Praxis issue includes four research papers, one innovative practice paper and one book review. It also includes some words from the editor in the period 2012–2022, Dr. Inés Gil-Jaurena, who steps down in her role and will be replaced in 2023 by a team led by Dr. Aras Bozkurt.